Performance of High-Strength Concrete Properties for Two Locally Available Aggregates: Partial Gradation Approaches - Pertiwi, Dewi; Agusdini, Theresia Maria Chandra; Komara, Indra; Wahyu, Ahmad (Trends in Sciences, 2023)
The aggregates in a concrete play a role in both strength and durability. Without a change of doubt, aggregates have a significant impact on mechanical, fresh and long-term performance properties of concrete. Low quality aggregates will give low behaviours that affect the condition of the concrete. In this investigation, improvement of local’s aggregate - natural mount sand and uncrushed mount gravel taken from Lumajang, Pasuran and Bangkalan, used as the parameter study. This study is conducted to support the low characteristics aggregate in terms of water absorption, sorptivity and compressive strength concrete. Three mixes variables are used based on w/c content, 0.40, 0.35 and 0.30 reflected the concrete quality. On the other hand, concrete mixes with locally grading group are 80 % aggregate from Bangkalan and 20 % aggregate from Lumajang or Pasuruan + Bangkalan (M4 and M5). The results indicated that the M4 and M5 grading group concrete mix had the maximum compressive strength out of the eight different concrete mixes. This particular mixture also improves the water absorption and sorptivity of the concrete. HIGHLIGHTS Ten concrete mixes with three concrete types were prepared using mount sand uncrushed mount gravel, with respect to understanding mechanical and physical properties comparing to 28-day compressive strength results. Those three mixes, M1, M2 and M3, provided to give the alternative of using unused coarse aggregate with low characteristic under three different w/c ratio i.e., 0.40, 0.35 and 0.30. Those conditions relate to the concrete quality - minimum compressive strength that normally used in the construction. Low characteristic aggregate, without a doubt impacting on long term performance properties of concrete structure. Locally available materials taken from Lumajang, Pasuruan and Bangkalan were used as the combined grading group of fine and coarse aggregate in each mixture. It was found that the optimum combine grading group was fine aggregate from Bangkalan + coarse aggregate from Lumajang or Pasuruan + Bangkalan (M4 and M5). Using M4 and M5 grading group, results indicated that, the highest compressive strength among the eight concrete mixes. In addition, these concrete mixes also illustrate to have low sportively and water absorption. GRAPHICAL ABSTRACT